2022
DOI: 10.1200/jco.21.02554
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Palbociclib for Early Breast Cancer: The PALLAS Trial Results (ABCSG-42/AFT-05/BIG-14-03)

Abstract: PURPOSE Palbociclib is a cyclin-dependent kinase 4 and 6 inhibitor approved for advanced breast cancer. In the adjuvant setting, the potential value of adding palbociclib to endocrine therapy for hormone receptor–positive breast cancer has not been confirmed. PATIENTS AND METHODS In the prospective, randomized, phase III PALLAS trial, patients with hormone receptor–positive, human epidermal growth factor receptor 2–negative early breast cancer were randomly assigned to receive 2 years of palbociclib (125 mg or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
84
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 48 publications
(65 reference statements)
1
84
0
8
Order By: Relevance
“…However, the duration of therapy varied; ribociclib was given for 3 years in NATALEE, 42 abemaciclib for 2 years in monarchE, 43 palbociclib for 2 years in PALLAS, and 1 year in PENELOPE-B, Table 2 . 44 , 45 …”
Section: Cdk4/6 Inhibitors In Adjuvant Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the duration of therapy varied; ribociclib was given for 3 years in NATALEE, 42 abemaciclib for 2 years in monarchE, 43 palbociclib for 2 years in PALLAS, and 1 year in PENELOPE-B, Table 2 . 44 , 45 …”
Section: Cdk4/6 Inhibitors In Adjuvant Settingmentioning
confidence: 99%
“…No specific subgroup seemed to benefit from the addition of palbociclib to ET. 44 At an earlier interim analysis, the independent data monitoring committee recommended discontinuing palbociclib in patients still receiving it. The AEs within the palbociclib arm were a major issue, with two-thirds of patients developing grade-3 or 4 AEs.…”
Section: Palbociclib Adjuvant Clinical Trialsmentioning
confidence: 99%
“…In 2021, Erica L Mayer and colleagues, 9 reported an interim analysis in The Lancet Oncology of the ongoing, global, phase 3 PALLAS trial, with the updated preplanned final analysis published in December, 2021. 10 Between Sept 1, 2015, and Nov 30, 2018, 5761 patients with early-stage breast cancer were randomly assigned (1:1) at 406 cancer centres in 21 countries to receive either 2 years of the CDK4/6 inhibitor palbociclib in addition to standard adjuvant endocrine therapy (n=2884) or adjuvant endocrine therapy alone (n=2877). 10 2841 patients received palbociclib plus endocrine therapy and 2901 patients received endocrine therapy only; 36 individuals were excluded.…”
mentioning
confidence: 99%
“… 10 Between Sept 1, 2015, and Nov 30, 2018, 5761 patients with early-stage breast cancer were randomly assigned (1:1) at 406 cancer centres in 21 countries to receive either 2 years of the CDK4/6 inhibitor palbociclib in addition to standard adjuvant endocrine therapy (n=2884) or adjuvant endocrine therapy alone (n=2877). 10 2841 patients received palbociclib plus endocrine therapy and 2901 patients received endocrine therapy only; 36 individuals were excluded. The safety analysis of the PALLAS trial showed no new signals of adverse events for palbociclib, with grade 3–4 neutropenia being the most prevalent (in 1742 [61·3%] of 2840 patients on palbociclib and endocrine therapy vs 11 [0·3%] of 2903 on endocrine therapy alone).…”
mentioning
confidence: 99%
See 1 more Smart Citation